Dampak Sosial Pengelolaan Batu Kapur terhadap Lingkungan Masyarakat Desa Lobong Kecamatan Passi Barat Kabupaten Bolaang Mongondow - Adisty Deanata Makalalag; Selvana Treny Rosita Tewal; Nixon Jefres Sindua (Fakultas Ilmu Sosial dan Hukum, 2023)
This research aims to describe the social impact of society on limestone management with the sub-focuses of (a) income, (b) welfare, and (c) community environment. This research uses qualitative methods. Data collection was done through observation and interviews. Data analysis techniques include reduction, presentation, and conclusion. The research results show that limestone processing impacts increasing income and creating jobs and welfare. The environmental impact caused by limestone processing is air pollution, namely dust. The government assesses that limestone processing impacts improving the community's economy, provided that it can protect the environment and impact the surrounding community in the form of sustainable prosperity.